Liquid and vapour-phase antifungal activities of essential oils against Candida albicans and non-albicans Candida. Issue 1 (December 2016) - Mandras, Narcisa; Nostro, Antonia; Roana, Janira; Scalas, Daniela; Banche, Giuliana; Ghisetti, Valeria; Del Re, Simonetta; Fucale, Giacomo; Cuffini, Anna; Tullio, Vivian
Abstract Background The management of Candida infections faces many problems, such as a limited number of antifungal drugs, toxicity, resistance of Candida to commonly antifungal drugs, relapse of Candida infections, and the high cost of antifungal drugs. Though azole antifungal agents and derivatives continue to dominate as drugs of choice against Candida infections, there are many available data referring to the anticandidal activity of essential oils. Since we have previous observed a good antimicrobial activity of some essential oils against filamentous fungi, the aim of this study was to extend the research to evaluate the activity of the same oils onCandida albicans, C.glabrata andC.tropicalis clinical strains, as well as the effects of related components. Essential oils selection was based both on ethnomedicinal use and on proved antibacterial and/or antifungal activity of some of these oils. Fluconazole and voriconazole were used as reference drugs. Methods The minimum inhibitory concentration (MIC) and the minimal fungicidal concentration (MFC) of essential oils (thyme red, fennel, clove, pine, sage, lemon balm, and lavender) and their major components were investigated by the broth microdilution method (BM) and the vapour contact assay (VC). Results Using BM, pine oil showed the best activity against all strains tested, thoughC.albicans was more susceptible thanC.glabrata andC.tropicalis (MIC50 -MIC90  = 0.06 %,  v/v). On the contrary, sage oil displayed a weak activity (MIC50 -MIC90  = 1 %, v/v). Thyme red oil (MIC50 -MIC90  ≤ 0.0038 %, v/v forC.albicans andC.tropicalis, and 0.0078- < 0.015 %, v/v forC.glabrata ), followed by lemon balm, lavender and sage were the most effective by VC. Carvacrol and thymol showed the highest activity, whereas linalyl acetate showed the lowest activity both by two methods. α-pinene displayed a better activity by BM than VC. Conclusion Results show a good activity of essential oils, mainly thymus red and pine oils, and their components carvacrol, thymol and α-pinene againstCandida spp., including fluconazole/voriconazole resistant strains. These data encourage adequately controlled and randomized clinical investigations. The use in vapour phase could have additional advantages without requiring direct contact, resulting in easy of environmental application such as in hospital, and/or in school.